Role of efflux pumps in reduced susceptibility to tigecycline in Acinetobacter baumannii - Ardehali, S.H. (New Microbes New Infect, 2019)
Acinetobacter baumannii is an important human pathogen responsible for a various type of infections. These bacterial strains are generally resistant to numerous antibiotics. Therefore, eradication of such strains is problematic and related to high mortality. We investigated the effect of cyanide 3-chlorophenylhydrazone (CCCP) efflux pump inhibitor in tigecycline-resistant strains of Acinetobacter baumannii. In a cross-sectional study, from July until the end of February 2017, eighty isolates of A. baumannii were recovered. Antimicrobial susceptibility testing against tigecycline was performed by the disc diffusion method and determination of minimum inhibitory concentration by broth microdilution method, according to Clinical and Laboratory Standards Institute guidelines. Active efflux pumps were detected by CCCP as an efflux pumps inhibitor, and the gene expression of some of the resistance/nodulation/division (RND)-type efflux pumps was measured by semiquantitative RT-PCR (qRT-PCR). Antibiotic susceptibility tests in this study showed that 78 of 80 A. baumannii isolates were resistant to tigecycline. The results of phenotypic detection of efflux pumps revealed that 23.07% of tigecycline-resistant A. baumannii isolates can contain active efflux pumps. On the basis of conventional PCR, genes coding for adeF and adeJ were detected in 76 (98%) A. baumannii isolates. The results of qRT-PCR showed that the transcript level of the adeJ gene increased in 66.6% A. baumannii isolates with CCCP-positive tests and was correlated with tigecycline resistance. The results of this study indicate that RND-type efflux pumps appear to play a significant role in the tigecycline resistance of A. baumannii.